UTILIZING MIND MAPPING TO ENHANCE WRITING SKILLS AND CULTURAL UNDERSTANDING THROUGH CREATIVE WRITING WORKSHOPS - Tesaannisa, Tesaannisa; Rakhman, Rizki Taufik; Leiliyanti, Eva; Prayitno, Eko Hadi; Diyantari, Diyantari; Fatkhiyati, Nurrahma Restia (JMM (Jurnal Masyarakat Mandiri), 2024)
Abstract: This community service project is a collaboration between the Faculty of Language and Arts, Jakarta State University, and the Cisaat Village Government, initiated by the English Literature Program in collaboration with the Visual Arts Education Program of the Faculty of Language and Arts, Jakarta State University. This community service project was conducted in Cilimus Village with the aim of enhancing participants' writing skills and their understanding of their own culture through a cultural knowledge strategy via creative writing training based on local wisdom, employing the technique of mind mapping. The subjects of this community service project were 17 students from Junior High School and Senior High School. The mind mapping technique was applied as a tool to organize ideas from Cilimus Village into creative writing pieces. The evaluation of the writing was carried out using a narrative writing rubric based on the Common Core State Standards (CCSS) W.7.3, assessing students' abilities in effective and comprehensive narrative writing. The evaluation results showed an increase in the number of participants who achieved a minimum score of 20 points, totaling 80% of all participants. The outcome of this community service project is creative writing by the young generation of Cilimus Village that reflects the cultural values and uniqueness of Cilimus Village, contributing to the preservation and promotion of Cilimus Village's cultural heritage.